Answer:
c. (-2, 5)
Step-by-step explanation:
y - 2 = 3/2(x + 4)
to know which is the correct option we have to replace the equation x and y with what is in the point
a.
y - 2 = 3/2(x + 4)
(-1) - 2 = 3/2((-2) + 4)
-3 = 3/2(2)
-3 = 3
Wrong
b.
y - 2 = 3/2(x + 4)
(5) - 2 = 3/2((-6) + 4)
3 = 3/2(-2)
3 = -3
Wrong
c.
y - 2 = 3/2(x + 4)
(5) - 2 = 3/2((-2) + 4)
3 = 3/2(2)
3 = 3
Correct
d.
y - 2 = 3/2(x + 4)
(-1) - 2 = 3/2((6) + 4)
-3 = 3/2(10)
-3 = 15
Wrong
Answer:
A&B
Step-by-step explanation:
Answer:
75 an 35 YEE YEE.
Step-by-step explanation:
im pretty sure
Answer:
i don't have and idea
Step-by-step explanation: